Superhydrophobic Pvdf Nmp Caco3 Nanoparticles Membrane For Membrane Filtration Of Oil Water Separation - Faudzi, Inas Irdina Mohd (Universiti Sains Malaysia, 2022)
Calcium carbonate, CaCO3, have been used widely for the application of membrane such as membrane distillation and membrane filtration. It is often used in various kind of membrane based like PVDF membrane which the priority of this introduction is to improve the morphology of the membrane to be used in particular process. PVDF membrane is known one of the membranes that have the hydrophobic properties but in order to enhance these properties, addition of other chemical substances can be helpful. PVDF membrane also possess high binding capacity which can prevents protein to pass through the membrane. Furthermore, in this research project, experiment have been conducted to change the hydrophobicity of PVDF membrane to have the ability of superhydrophobic membrane properties by addition of CaCO3 nanoparticles. This addition will cause changes in water contact angle, porosity and also improve our target to do filtration for oily wastewater. In this project, different concentration of CaCO3 was used which ranged from (1-6 wt%) with constant weight percent of NMP solvent. Membrane characterization were performed using the water contact angle, membrane porosity and oil rejection percentage were calculated. The mixture of different concentration of CaCO3 causes the water contact angle to be range from 148.5º to 154.6º which gives the membrane a superhydrophobic properties. Membrane porosity for all membrane showed value more than 80% which indicates the addition of nanoparticles does change the morphology of the membrane. The highest oil rejection from membrane was 101.1% which showed that the addition of nanoparticles will increase the superhydrophobic properties of the membranes. In this research project, the higher the concentration of nanoparticles, does not produce better oil rejection of the membrane due to the increasing of the oil particles in the membrane pore. Thus, we conclude that introducing of CaCO3 nanoparticles in PVDF membrane have promising results in oily wastewater filtration with inserting more antifouling properties and mechanical strength.